Sacred species and sites advances in biocultural conservation - Pungetti, Gloria; Oviedo, Gonzalo; Hooke, Della (Cambridge, UK ; New York : Cambridge University Press, 2012)
"It is being increasingly recognised that cultural and biological diversity are deeply linked and that conservation programmes should take into account the ethical, cultural and spiritual values of nature. With contributions from a range of scholars, practitioners and spiritual leaders from around the world, this book provides new insights into biocultural diversity conservation. It explores sacred landscapes, sites, plants and animals from around the world to demonstrate the links between nature conservation and spiritual beliefs and traditions. Key conceptual topics are connected to case studies, as well as modern and ancient spiritual insights, guiding the reader through the various issues from fundamental theory and beliefs to practical applications. It looks forward to the biocultural agenda, providing guidelines for future research and practice and offering suggestions for improved integration of these values into policy, planning and management"--
Machine generated contents note: Part I. Concepts and Knowledge; Part II. Sacred Landscapes; Part III. Sacred Sites and People; Part IV. Sacred Species; Part V. Sacred Animals; Part VI. Sacred Groves and Plants; Part VII. Implementation and Conclusions.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Sacred space; Human ecology -- Religious aspects; Conservation of natural resources -- Religious aspects; Plants -- Religious aspects; Animals -- Religious aspects; NATURE / Ecology; RELIGION / Reference; Electronic books